Bridging the green gap in homesharing: how platforms can increase hosts’ sustainability intentions and behavior - Sandoval Álvarez, Carlos Alberto (2024)
Homesharing platforms are under substantive pressure to become more environmentally sustainable. Key to this challenge is these platforms’ homesharing hosts, who have the opportunity to introduce new sustainability innovations (e.g., water-saving measures). However, knowledge of what drives hosts’ sustainability behavior is currently limited. We address this gap and investigate antecedents for hosts’ sustainability intentions. Our study is based on a survey in Europe (conducted in 12 languages), resulting in a sample of 1,392 hosts. Building on the theory of planned behavior, we perform three analyses: (a) quantitative and theory testing, (b) quantitative and explorative, and (c) qualitative and explorative. Notably, we find that attitude and norms, as well as financial resources and time, are the main drivers of hosts’ sustainability intentions. In addition, the presence of local service offices (i.e., a platform business model that internalizes service operations from hosts) moderates the effects of sustainability antecedents.